Jorge el curioso y los bomberos = Curious George and the firefighters - Rey, H. A. (Hans Augusto), 1898-1977.; Rey, Margret; Hines, Anna Grossnickle (Boston : Houghton Mifflin Harcourt, 2010)
While on a field trip to a fire station with Mrs. Gray's class, Curious George goes off on his own and is soon at the scene of a fire, where he finds a way to be helpful.
In English and Spanish.
Keywords: Monkeys -- Juvenile fiction; Fire fighters -- Juvenile fiction; Fire departments -- Juvenile fiction; Spanish language materials -- Bilingual; Spanish language materials -- Juvenile literature